2016
DOI: 10.1038/srep38135
|View full text |Cite
|
Sign up to set email alerts
|

Five key attributes can increase marine protected areas performance for small-scale fisheries management

Abstract: Marine protected areas (MPAs) have largely proven to be effective tools for conserving marine ecosystem, while socio-economic benefits generated by MPAs to fisheries are still under debate. Many MPAs embed a no-take zone, aiming to preserve natural populations and ecosystems, within a buffer zone where potentially sustainable activities are allowed. Small-scale fisheries (SSF) within buffer zones can be highly beneficial by promoting local socio-economies. However, guidelines to successfully manage SSFs within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 50 publications
3
153
1
4
Order By: Relevance
“…Ideally, all stakeholder groups should be involved in the process; in practice, however, this is rarely possible. Therefore, specific groups, whose compliance is crucial for MPA effectiveness, e.g., small-scale fishing co-operatives and local government (Beger et al, 2004;Di Franco et al, 2016), should be targeted.…”
Section: Stakeholder Engagementmentioning
confidence: 99%
“…Ideally, all stakeholder groups should be involved in the process; in practice, however, this is rarely possible. Therefore, specific groups, whose compliance is crucial for MPA effectiveness, e.g., small-scale fishing co-operatives and local government (Beger et al, 2004;Di Franco et al, 2016), should be targeted.…”
Section: Stakeholder Engagementmentioning
confidence: 99%
“…Different levels of partial protection, together with full protection, can be combined spatially within multiple-use MPAs. Accordingly, the capacity of MPAs to reduce threats will differ depending on their type, design, regulations and level of enforcement (Di Franco et al, 2016;Guidetti et al, 2008;Scianna et al, 2015). Therefore, information on the intensity of threats within each MPA zone and in the surrounding external areas is necessary to assess MPA effectiveness in reducing threats.…”
Section: Introductionmentioning
confidence: 99%
“…This mature stage is inevitable, as succession is a process of self-organization (Fath et al, 2004). Empirical studies in Mediterranean MPAs (García-Charton et al, 2004;Tudela et al, 2005;Coll et al, 2013;García-Rubies et al, 2013;Guidetti et al, 2014) showed how fish communities undergo a huge increase in target biomass-usually piscivore species within core marine reserve areas, and restoring a more "natural" community structure, provided that they are well enforced (Guidetti et al, 2008;Di Franco et al, 2016). All this leads to the general view that Mediterranean MPAs are almost always successful in achieving the planned objectives.…”
Section: Fish Box Vs Mpasmentioning
confidence: 99%
“…The interest of MPAs as fishery management tool lies mostly on their potential to improve artisanal fisheries of high-value species in surrounding fishing grounds (Kerwath et al, 2013;Di Franco et al, 2016;Lloret et al, 2017). At the same time, they intend to favor the economic development of the area through the establishment of services related to tourism and diving activities providing an alternative source of inputs also for fishermen (Angulo-Valdés and Hatcher, 2010;Rees et al, 2015;Pascual et al, 2016).…”
Section: Mpas As Fisheries Management Toolmentioning
confidence: 99%